Covering material

JP2025021989APending Publication Date: 2025-02-14F CONSULTANT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023126148
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

Smart Images

  • Figure 2025021989000001
    Figure 2025021989000001
Patent Text Reader

Abstract

To provide a covering material that secures a sufficient working time (pot life) in the covering material and allows for the formation of a thick film without defects such as cracks.SOLUTION: A covering material contains, as a coating-forming component (A), a polyol component (A1) and a polyisocyanate component (A2), and further contains a powder component (B). Relative to 100 pts.mass of the coating-forming component (A), the powder component (B) is 100 pts.mass or more. The powder component (B) contains fatty acid-coated powder (B-1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel coating material. [Background technology]

[0002] Conventionally, urethane coating materials consisting of polyol and polyisocyanate components have been used in a wide range of applications, such as anticorrosive paints, fireproof paints, waterproof paints, floor paints (flooring materials), sealants, and paving materials. These coating materials may form thick films to enhance their properties. To form a thick film, the coating material must be applied multiple times, which poses the problem of a long construction period. On the other hand, coating materials that can form thick films with a single coat have also been developed. For example, Patent Document 1 describes a two-liquid coating composition that uses a vinyl resin of a specific molecular weight and a hydroxyl group-containing resin in combination, and that can be made high solid by mixing a composition containing a catalyst and a polyisocyanate compound immediately before use. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-109753 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the case of high-solid paints containing a large amount of resin components, such as those in Patent Document 1, thicker films can be produced by increasing the reactivity of the resin through the addition of an appropriate amount of catalyst. However, in coating materials that contain a small amount of resin components and a large amount of powder components such as pigments and fillers, for example, when a catalyst is added to enhance the reactivity of the resin, it may not be possible to ensure a sufficient pot life. In particular, in high temperature environments, this may lead to a decrease in coating workability and a risk of impairing the appearance and physical properties of the formed coating. On the other hand, when trying to secure a pot life, the reactivity of the resin decreases, and cracks may occur when forming a thick film. In particular, in a low temperature to room temperature environment, if the reactivity of the resin decreases, it becomes difficult to form a thick film. In this way, it is difficult to achieve both pot life and crack resistance when forming a thick film, and there is room for improvement.

[0005] The present invention has been made in consideration of such problems, and has an object to provide a coating material that can ensure a sufficient pot life of the coating material and that can form a thick film without causing defects such as cracks. [Means for solving the problem]

[0006] In order to solve these problems, the present inventors discovered that by including a powder coated with a specific component in a coating material, the usable time (pot life) of the coating material can be sufficiently ensured and furthermore, a thick film can be formed without causing defects such as cracking, thereby completing the present invention.

[0007] That is, the present invention has the following features. 1. A coating material comprising a polyol component (A1) and a polyisocyanate component (A2) as a film-forming component (A), and further comprising a powder component (B), The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The coating material, wherein the powder component (B) contains a powder (B-1) coated with a fatty acid. 2. The coating material according to 1., wherein the powder (B-1) is contained in an amount of 2 to 80 mass% based on the total amount of the powder component (B). 3. A base material containing the polyol component (A1) and the powder component (B); A curing agent containing the polyisocyanate component (A2); 3. The coating material according to 1. or 2., which is a multi-component coating material having the following formula: Effect of the Invention

[0008] The present invention relates to a coating material comprising, as a film-forming component (A), a polyol component (A1) and a polyisocyanate component (A2), and further comprising a powder component (B). By including, as the powder component (B), a powder (B-1) coated with a fatty acid, the usable time (pot life) of the coating material can be sufficiently ensured, and furthermore, a thick film can be formed without causing defects such as cracks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below based on the embodiments.

[0010] The coating material of the present invention contains a polyol component (A1) and a polyisocyanate component (A2) as a coating-forming component (A). The polyol component (A) and the polyisocyanate (A2) are components that react with each other to form a coating.

[0011] In the present invention, examples of the polyol component (A1) include polyester polyols, polyether polyols, polycarbonate polyols, polylactone polyols, polybutadiene polyols, polypentadiene polyols, castor oil, castor oil-based polyols, fluorine-containing polyols, and acrylic polyols, and one or more of these can be used.

[0012] Examples of the polyester polyol include aromatic polyester polyol, aliphatic polyester polyol, and aromatic / aliphatic polyester polyol.

[0013] Specifically, the aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting a saturated aliphatic polybasic acid such as succinic acid, adipic acid, azelaic acid, or sebacic acid with a polyhydric alcohol, and condensation polyester polyols obtained by reacting an unsaturated aliphatic polybasic acid such as maleic acid or fumaric acid with a polyhydric alcohol.

[0014] The aromatic polyester polyol is a polyol having an aromatic hydrocarbon in one molecule, and examples thereof include condensed polyester polyols obtained by reacting an aromatic polybasic acid such as orthophthalic acid, isophthalic acid, terephthalic acid, phthalic anhydride, etc. with a polyhydric alcohol, and phthalic acid-based polyester polyols obtained by decomposing a phthalic acid-based polyester molded product such as polyethylene terephthalate, etc. In addition, examples of the polyhydric alcohol include dihydric or higher alcohols and derivatives thereof, dihydric or higher phenols, polyols, etc.

[0015] The aromatic / aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon and an aromatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting an aromatic polybasic acid or an aliphatic polybasic acid with a polyhydric alcohol.

[0016] Examples of the polyether polyol include aromatic polyether polyols, phosphorus-containing polyether polyols, glycerin-based polyether polyols, and amino group-containing polyether polyols.

[0017] Examples of the aromatic polyether polyol include bisphenol A-type polyether polyols obtained by adding an alkylene oxide (e.g., ethylene oxide, propylene oxide, etc.) to bisphenol A as an initiator, and aromatic amine-based polyether polyols obtained by adding an alkylene oxide to an aromatic amine (e.g., toluenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, p-phenylenediamine, o-phenylenediamine, naphthalenediamine, triethanolamine, Mannich condensation products, etc.) as an initiator.

[0018] Examples of the phosphorus-containing polyether polyol include dialkyl-N,N-bis(2-hydroxyethyl)aminomethylphosphonate, which is a diol having a phosphoric acid ester structure.

[0019] The glycerin-based polyether polyols include polyether polyols obtained by adding alkylene oxide to glycerin as an initiator.

[0020] Examples of the amino group-containing polyether polyol include those obtained by adding an alkylene oxide to a low molecular weight amine (for example, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, neopentyldiamine, etc.) as an initiator.

[0021] The castor oil-based polyol is a polymer derived from castor oil or castor oil fatty acid, and examples thereof include alkylene oxide adducts of castor oil or castor oil fatty acid, epoxidized products of castor oil or castor oil fatty acid, halides of castor oil or castor oil fatty acid, transesterification products of castor oil or castor oil fatty acid and polyhydric alcohol, and hydrogenated products thereof. In the present invention, castor oil-based polyols and / or castor oil are particularly preferred, and it is more preferred that they contain castor oil.

[0022] The fluorine-containing polyol may be a copolymer of a fluorine-containing monomer, such as a fluoroolefin monomer or a fluoroalkyl group-containing acrylic monomer, a hydroxyl group-containing vinyl monomer, and, if necessary, another polymerizable monomer.

[0023] In particular, in the present invention, it is preferable that the polyol component (A) contains a polyether polyol. The content of the polyether polyol is preferably 50 mass% or more (more preferably 60 to 100 mass%, and further preferably 70 to 98 mass%) based on the total amount of the polyol component (A).

[0024] The hydroxyl value of the polyol in the present invention is not particularly limited, but is preferably 3 to 150 mgKOH / g or more, more preferably 5 to 100 mgKOH / g, further preferably 7 to 40 mgKOH / g, and most preferably 10 to 30 mgKOH / g. Note that, in the present invention, the hydroxyl value is a value (mgKOH / g) represented by the number of mg of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of solid content, and "α to β" is synonymous with "α or more and β or less".

[0025] The polyisocyanate component (A2) of the present invention has two or more isocyanate groups in one molecule and reacts with the polyol to form a coating film, and various known isocyanates can be used.

[0026] Examples of the polyisocyanate component include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, etc., and derivatives thereof by allophanation, biuretization, dimerization (uretidione), trimerization (isocyanurate), adductation, carbodiimide reaction, etc., mixtures thereof, and copolymers thereof with monomers copolymerizable therewith, etc. These can be used alone or in combination of two or more.

[0027] Examples of the aliphatic diisocyanate include 1,3-trimethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,3-pentamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HMDI), 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, and 1,3-butylene diisocyanate. anate, 2-methyl-1,5-pentamethylene diisocyanate, 3-methyl-1,5-pentamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.

[0028] Examples of the alicyclic diisocyanate include 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, isophorone diisocyanate (IPDI), norbornane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, and hydrogenated xylylene diisocyanate.

[0029] Examples of the aromatic diisocyanate include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate (TDI), naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 4,4'-diphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4'-diphenylmethane diisocyanate, Examples of the isocyanate include 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylene xylylene diisocyanate.

[0030] Examples of the aromatic aliphatic diisocyanate include 1,3-xylylene diisocyanate (XDI), 1,4-xylylene diisocyanate (XDI), ω,ω'-diisocyanate-1,4-diethylbenzene, 1,3-bis(1-isocyanate-1-methylethyl)benzene, 1,4-bis(1-isocyanate-1-methylethyl)benzene, and 1,3-bis(α,α-dimethylisocyanate methyl)benzene.

[0031] In the present invention, it is particularly preferable to contain an aliphatic diisocyanate such as HMDI and its derivatives. The content of the HMDIs is preferably 90% by mass or more (more preferably 95% by mass or more) based on the total amount of the polyisocyanate component (A2).

[0032] The polyol component (A1) and the polyisocyanate component (A2) are mixed in such a ratio that the NCO / OH equivalent ratio of the polyol component (A1) and the polyisocyanate component (A2) is preferably 0.6 to 3.5 (more preferably 1 to 3.0, and even more preferably 1.1 to 2.5). In such a case, a coating film having excellent curability and a uniform thickness of a desired thickness can be formed. Furthermore, the formed coating film has excellent durability (e.g., waterproofness, water impermeability, crack resistance, conformability to substrate, etc.) and can maintain the initial appearance (beauty) for a long period of time.

[0033] In the present invention, a curing catalyst (P) that promotes the reaction between the polyol component (A1) and the polyisocyanate component (A2) can be used in combination. The curing catalyst (P) is a substance that promotes the reaction of isocyanate groups to cause curing. Examples of the curing catalyst (P) include various types of amine catalysts, organometallic catalysts, and inorganic catalysts. Examples of amine catalysts include ethylenediamine, triethylenediamine, triethylamine, ethanolamine, diethanolamine, and hexamethylenediamine, or derivatives thereof, or mixtures thereof with solvents. Examples of organometallic catalysts include organometallic compounds such as dibutyltin dilaurate and dibutyltin diacetate; and organometallic salts such as potassium acetate, zinc stearate, calcium stearate, lead stearate, aluminum stearate, and tin octylate. Examples of inorganic catalysts include tin chloride. These can be used alone or in combination, and can also be used by mixing with a solvent. In the present invention, it is particularly preferable to contain an organometallic catalyst (most preferably dibutyltin dilaurate or dibutyltin diacetate), which can accelerate curing and further enhance the curability of the film-forming component.

[0034] The amount of the curing catalyst (P) is preferably 0.05 to 3 parts by mass (more preferably 0.08 to 2.8 parts by mass, and even more preferably 0.1 to 2.5 parts by mass) of the active ingredient per 100 parts by mass of the solid content of the film-forming component (A). In this case, the crosslinking reaction of the film-forming component (A) can be sufficiently promoted. The amount of the curing catalyst (P) can be set according to the coating environment.

[0035] The coating material of the present invention further contains a powder component (B), and is characterized in that the powder component (B) is contained in an amount of 100 parts by mass or more (preferably 100 to 1000 parts by mass, more preferably 150 to 800 parts by mass) per 100 parts by mass of the solid content of the film-forming component (A). The powder component (B) is blended according to the application of the coating material (for example, anticorrosive paint, fireproof paint, waterproof paint, floor paint (floor material), sealing material, paving material, putty material, etc.), and known powders can be used. Examples of such powder component (B) include various pigments (coloring pigments, extender pigments, functional pigments, etc.), fibers, functionality-imparting powders, etc. These can be used alone or in combination of two or more kinds.

[0036] Furthermore, the powder component (B) is characterized by including powder (B-1) coated with a fatty acid (hereinafter, simply referred to as "coated powder (B-1)"). By including such coated powder (B-1), the pot life of the coating material is sufficiently secured, and a thick film can be formed without causing defects such as cracking. Although the mechanism of action is not limited, by blending powder component (B-1) coated with a fatty acid, the carbonyl group of the fatty acid has the effect of primarily masking the isocyanate group of polyisocyanate component (A2) in the coating material. This reduces the reactivity of the isocyanate group (NCO group) of polyisocyanate component (A2), thereby extending the pot life. In addition, in the coating material of the present invention, the NCO group of the polyisocyanate component (A2) may undergo a reaction with the OH group of the polyol component (A1) to form a urethane bond (resinification reaction), and may also undergo a reaction with moisture (humidity, etc.) in the air to generate carbon dioxide and form a urea bond (foaming reaction). In the present invention, the above-mentioned masking action can efficiently suppress the reaction with water, which has a high reactivity ranking (foaming reaction). As a result, it is presumed that the reaction with the polyol component (A1) (resinification reaction) can be sufficiently advanced, and therefore a thick film can be formed without cracking or the like. Furthermore, even in the case of the present invention in which a large amount of powder component (B) is contained relative to the coating component (A) (resin component), the inclusion of the coating powder (B-1) ensures a sufficient pot life, thereby making it possible to improve the workability and the appearance and physical properties of the formed coating. Such an effect is exhibited even when a curing catalyst (P) is blended into the coating material. Therefore, it is possible to blend an optimum amount of the curing catalyst (P) into the coating material of the present invention in order to promote the resinification reaction. This makes it possible to form a thick film without causing cracks or the like while ensuring a sufficient pot life, thereby improving the appearance and physical properties of the formed coating.

[0037] In the present invention, it is preferable that the powder component (B) contains the coated powder (B-1) in an amount of 2 to 80 mass % (more preferably 3 to 70 mass %, further preferably 5 to 65 mass %, particularly preferably 10 to 60 mass %) based on the total amount of the powder component (B). In this case, the effects of the present invention can be further enhanced.

[0038] Examples of fatty acids that coat the powder component (B) include saturated fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachic acid, behenic acid, cerotic acid, and melissic acid; unsaturated fatty acids such as palmitreic acid, oleic acid, elaidic acid, erucic acid, linoleic acid, linoleic acid, eleostearic acid, and sardine acid; and fatty acid derivatives such as hydroxystearic acid and dimer acid. These can be used alone or in combination. In the present invention, it is preferable to use one or more saturated fatty acids selected from capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachic acid, behenic acid, cerotic acid, and melissic acid. Furthermore, it is preferable for the fatty acid to have 6 or more carbon atoms (more preferably 7 to 26, particularly preferably 8 to 24), and it is particularly preferable for the fatty acid to have 12 or more carbon atoms (preferably 12 to 24).

[0039] The method for coating the surface of the powder with the fatty acid is not particularly limited, but examples thereof include a method in which the molten fatty acid is mixed with the powder, followed by drying and pulverization, or a method in which the fatty acid and the powder are added to a solvent such as isopropyl alcohol or ethanol, mixed, and then dried and pulverized. In addition, the amount of fatty acid coated (hereinafter also referred to as "coating rate") is preferably 0.1 to 10% by mass (more preferably 0.2 to 8% by mass) relative to the powder component. In such a range, the particle surface of the powder component can be sufficiently coated, the usable time (pot life) of the coating material can be sufficiently secured, and it is also preferable in terms of water repellency, dispersibility, stability, etc. In addition, by preventing the coating amount from becoming excessive, it is possible to prevent the excess fatty acid from being liberated, which can cause poor dispersibility or the generation of impurities.

[0040] The coated powder (B-1) may be any embodiment in which at least one of the above powder components (B), such as various pigments (coloring pigments, extender pigments, functional pigments, etc.), fibers, functionality-imparting powders, etc., is coated with a fatty acid (B-1). Specific embodiments include the following. The pigment includes a powder coated with a fatty acid. The fiber comprises a powder coated with a fatty acid. The functional powder includes a powder coated with a fatty acid. - A combination of two or more of the above. etc.

[0041] Examples of the pigment include inorganic color pigments such as titanium oxide, zinc oxide, carbon black, ferric oxide (red oxide), molybdate orange, yellow iron oxide, ultramarine, cobalt green, iron-chromium composite oxide, manganese-bismuth composite oxide, manganese-yttrium composite oxide, and manganese-iron-cobalt composite oxide; organic color pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone; functional pigments such as pearl pigments, fluorescent pigments, phosphorescent pigments, metallic pigments, and rust-preventive pigments; and extender pigments (fillers) such as heavy calcium carbonate, precipitated calcium carbonate, kaolin, talc, clay, china clay, china clay, barium sulfate, barium carbonate, silica powder, and diatomaceous earth. These can be used alone or in combination of two or more.

[0042] Examples of the fibers include organic fibers such as acrylic fibers, acetate fibers, aramid fibers, cuprammonium fibers (cupra), nylon fibers, novoloid fibers, pulp fibers, viscose rayon, vinylidene fibers, polyester fibers, polyethylene fibers, polyvinyl chloride fibers, polychlar fibers, boronosic fibers, polypropylene fibers, and cellulose fibers, and inorganic fibers such as carbon fibers, rock wool fibers, glass fibers, silica fibers, alumina fibers, silica-alumina fibers, slag wool fibers, ceramic fibers, carbon fibers, and silicon carbide fibers. These can be used alone or in combination of two or more.

[0043] In the case of a fire-resistant coating, examples of the functionality-imparting powder include a foaming agent, a carbonizing agent, and a flame retardant, etc. These are components that form a carbonized heat insulating layer by interacting with the coating-forming component (A) (e.g., at least one of a dehydration and cooling effect, a non-flammable gas generating effect, a carbonization promotion effect, a carbonized heat insulating layer forming effect, etc.), and can impart fire resistance.

[0044] The foaming agent imparts foaming action to the coating when the temperature rises during a fire or the like (for example, when the coating temperature reaches 200°C or higher). Examples of foaming agents include melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, thiourea, etc. These can be used alone or in combination of two or more.

[0045] The carbonizing agent is a material that imparts the effect of forming a carbonized heat insulating layer by carbonizing the film-forming component (A) and dehydrating and carbonizing it due to a temperature rise during a fire, etc. Examples of the carbonizing agent include pentaerythritol, dipentaerythritol, trimethylolpropane, starch, casein, etc. These can be used alone or in combination of two or more.

[0046] Examples of the flame retardant include organic phosphorus compounds, chlorine compounds, antimony compounds, phosphorus compounds, boric acid compounds, metal hydrates, etc. As the flame retardant, particularly phosphorus compounds are suitable, and examples thereof include ammonium phosphate, ammonium polyphosphate, melamine-coated ammonium polyphosphate, melamine phosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, boron phosphate, boron polyphosphate, aluminum phosphate, aluminum polyphosphate, etc. These can be used alone or in combination of two or more.

[0047] The coating material of the present invention may contain various additives as components other than those described above. Such additives may be any additives that do not significantly impair the effects of the present invention, and examples of such additives include wetting agents, plasticizers, lubricants, preservatives, antifungal agents, anti-algae agents, antibacterial agents, water absorbing agents, thickeners, leveling agents, dispersants, defoamers, crosslinking agents, silane coupling agents, ultraviolet absorbers, light stabilizers, antioxidants, halogen scavengers, diluting solvents, etc.

[0048] The heating residue of the coating material of the present invention is preferably 70 to 98 mass % (more preferably 75 to 95 mass %, and even more preferably 80 to 93 mass %). When the heating residue of the coating material satisfies the above range, excellent thick coating property and good coating workability can be obtained. The heating residue of the coating material is a value measured by the method of JIS K 5601-1-2, the heating temperature is 105°C, and the heating time is 60 minutes.

[0049] In the present invention, the viscosity of the coating material is preferably 5 to 70 Pa·s (more preferably 7 to 60 Pa·s, even more preferably 10 to 50 Pa·s, and particularly preferably 15 to 40 Pa·s). When the viscosity of the coating material satisfies the above range, the coating material has excellent workability and thick coatability, and a uniform coating film can be formed. The viscosity of the coating material is the viscosity at 20 rpm (guideline value at the fifth rotation) measured with a BH type viscometer at a temperature of 23°C immediately after the coating material is prepared (after mixing the base agent and curing agent in the case of a two-component type).

[0050] In the present invention, by applying a coating material that satisfies the above-mentioned ranges of heating residue and viscosity to form a coating, it is possible to further increase the thickness of the coating, and to stably form a uniform coating that exhibits good adhesion to the substrate.

[0051] The coating material of the present invention is preferably a multi-component coating material having a base agent containing the polyol component (A1) and a curing agent containing the polyisocyanate component (A2). That is, during distribution, the base agent and the curing agent are stored in separate packages, and are mixed when used (applied). The powder component (B) may be mixed with at least one of the base agent and the curing agent, but in the present invention, it is preferable to mix it with the base agent. Each component may also be added when mixing the base agent and the curing agent.

[0052] The coating material of the present invention is suitable as a coating material applied to the surface coating of structures such as buildings and civil engineering structures. Specifically, it can be applied to various substrates such as walls, pillars, floors, beams, roofs, stairs, ceilings, and doors. Applicable substrates include, for example, concrete, mortar, siding boards, extrusion molding boards, gypsum boards, perlite boards, bricks, plastics, wood, metals, steel frames (steel materials), glass, and porcelain tiles. These substrates may have a coating already formed on their surfaces, may have been subjected to some kind of surface treatment (rust prevention treatment, flame retardant treatment, etc.), or may have wallpaper attached thereto.

[0053] When applying (painting) the coating material of the present invention to a substrate, an application tool such as a spray, roller, brush, or trowel can be used.

[0054] When the coating material of the present invention is applied to a substrate, it may be applied by one or several steps by the above method, but it is preferable to apply so that the dry film thickness per step is preferably 400 μm or more (more preferably 500 to 8000 μm). The final coating thickness may be appropriately set depending on the desired functionality, application site, etc., but is preferably about 0.4 to 8 mm. In addition, the coating material of the present invention has excellent curing properties because it forms a coating by the reaction of the above component (A1) and the above component (A2), and the drying is preferably performed at room temperature, and the interval between the next step is preferably 5 hours or more (more preferably 10 hours or more and up to 30 days).

[0055] When applying the coating material of the present invention, if necessary, the substrate may be subjected to surface treatment or a primer may be applied before applying the coating material. This can improve adhesion to the substrate and corrosion resistance (rust resistance), etc. Surface treatment of the substrate may include, for example, surface treatment with a solvent or acid, scraping with a disk sander, wire foil, scraper, wire brush, sandpaper, etc.

[0056] As the undercoat material, for example, a sealer, a primer, a base conditioner, a surfacer, a putty, etc., as well as a flat-type paint can be applied. These may be either clear type or colored type. In addition, either water-based or solvent-based may be used, and can be appropriately selected according to the painting location, etc., and one or more types can be used. As the undercoat material, for example, it is preferable to contain a resin component such as an acrylic resin, a urethane resin, an epoxy resin, etc., and in addition to the above-mentioned resin components, various additives can be blended to an extent that does not affect the effect of the present invention. Examples of such additives include anti-rust pigments, extender pigments, coloring pigments, plasticizers, preservatives, anti-mold agents, anti-algae agents, defoamers, leveling agents, pigment dispersants, anti-settling agents, anti-sagging agents, antioxidants, catalysts, coupling agents, crosslinking agents, etc.

[0057] The undercoat material can be applied by various methods, such as brush coating, roller coating, spray coating, etc. The amount of application is preferably 30 to 500 g / m 2 (More preferably 50 to 300 g / m 2 The number of times the undercoat material is applied may be appropriately determined depending on the surface condition of the substrate, etc., but is preferably 1 to 2 times.

[0058] Furthermore, in the present invention, a finishing material layer can be laminated on the covering material layer (coating) formed by the above-mentioned covering material. Such a finishing material layer is not particularly limited, and a known finishing material can be laminated. Such a finishing material layer can be laminated by applying a topcoat material or by attaching various sheet materials or wooden boards (wooden surface materials), etc.

[0059] As the above-mentioned topcoat material, any of clear type or colored type, glossy type or matte type, hard type or elastic type, thin film type or thick film type can be used. In addition, it may be either water-based or solvent-based, and can be appropriately selected according to the desired purpose. In addition, it is preferable that the topcoat material of the present invention contains a resin component. Examples of the form of such a resin include solvent-soluble resin, non-water-dispersed resin, solventless resin, water-dispersed resin, water-soluble resin, etc. Examples of the type of resin include acrylic resin, urethane resin, epoxy resin, vinyl chloride resin, vinyl acetate resin, acrylic silicone resin, fluororesin, silicon resin, polyvinyl alcohol, cellulose derivatives, etc., or composites thereof. These can be used alone or in combination of two or more. In particular, in the present invention, it is preferable to include one or more selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin.

[0060] Furthermore, the resin component may have crosslinking reactivity. When the resin component is a crosslinking reactive resin, the water resistance, durability, and adhesion of the formed coating are improved, and the occurrence of swelling and peeling of the coating due to rainfall, condensation, etc. and the decrease in heat resistance can be suppressed. Such a crosslinking reactive resin may be either one that causes a crosslinking reaction by itself or one that causes a crosslinking reaction by a crosslinking agent that is mixed separately. Such crosslinking reactivity can be imparted by combining reactive functional groups such as, for example, a hydroxyl group and an isocyanate group, a carbonyl group and a hydrazide group, an epoxy group and an amino group, an aldo group and a semicarbazide group, a keto group and a semicarbazide group, alkoxyl groups, a carboxyl group and a metal ion, a carboxyl group and a carbodiimide group, a carboxyl group and an epoxy group, a carboxyl group and an aziridine group, or a carboxyl group and an oxazoline group. Among these, it is preferable to include one or more crosslinking reactive resins selected from a hydroxyl group-isocyanate group, a carbonyl group and a hydrazide group, and an epoxy group and an amino group.

[0061] As components other than the resin component of the above-mentioned topcoat material, for example, color pigments, extender pigments, aggregates, etc. can be mixed. By appropriately blending such components, it is possible to express the desired color and texture. The amount of color pigments, extender pigments, aggregates, etc. to be mixed is not particularly limited as long as it is within a range that does not inhibit the functionality (e.g., foamability, heat resistance protection, etc.) of the above-mentioned coating material, but is preferably 1 to 2000 parts by mass (more preferably 5 to 1000 parts by mass) relative to 100 parts by mass of the solid content of the resin component.

[0062] In the present invention, it is particularly preferable to use pigments having infrared reflectivity and / or infrared transmittance as the color pigments and extender pigments, which can further enhance the effects of heat resistance protection and the like.

[0063] Examples of pigments having infrared reflectivity include aluminum flakes, titanium oxide, barium sulfate, zinc oxide, iron oxide, calcium carbonate, silicon oxide, magnesium oxide, zirconium oxide, yttrium oxide, indium oxide, alumina, iron-chromium composite oxide, manganese-bismuth composite oxide, manganese-yttrium composite oxide, black iron oxide, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and the like, and one or more of these can be used.

[0064] Examples of pigments having infrared transmittance include perylene pigments, azo pigments, yellow lead, titanium red, cadmium red, quinacridone red, isoindolinone, benzimidazolone, phthalocyanine green, phthalocyanine blue, cobalt blue, indanthrene blue, ultramarine, and Prussian blue, and one or more of these can be used.

[0065] Furthermore, the topcoat material can also contain various additives that can be used in normal paints. Examples of such additives include thickeners, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, defoamers, adsorbents, ultraviolet absorbers, light stabilizers, antioxidants, fibers, low-pollution agents, hydrophilizing agents, water repellents, coupling agents, catalysts, etc.

[0066] In the present invention, the topcoat material can be applied by repainting, or two or more types of topcoat materials can be laminated and applied. When two or more types of topcoat materials are laminated, it is preferable that the first topcoat material (intermediate coating material) contains one or more resin components selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin (particularly preferably, urethane resin, epoxy resin, etc.). This can further increase the adhesion between the layers of the coating material and the topcoat material. Furthermore, a topcoat material coating with excellent coating properties can be formed.

[0067] The topcoat material may be applied by a known application method, for example, by using various methods such as brush coating, roller coating, spray coating, etc. The amount of coating is preferably 30 to 5000 g / m 2 (More preferably 50 to 3000 g / m 2 The number of times the topcoat material is applied may be set appropriately depending on the surface condition of the substrate, but is preferably 1 to 2 times. Drying may be preferably performed at room temperature.

[0068] Examples of the sheet material include decorative films, decorative sheets, sheet building materials, wallpapers, etc. The thickness of the sheet material is preferably 0.01 to 30 mm (more preferably 0.05 to 20 mm). These may be attached via a known adhesive (pressure-sensitive adhesive) or the like. EXAMPLES

[0069] The following examples will clarify the features of the present invention, but the present invention is not limited to these examples.

[0070] The following raw materials were used:

[0071] <Polyol component (A1)> Polyether polyol (addition polymer of ethylene oxide and propylene oxide with glycerin as initiator, number average molecular weight 7000, functionality 3, hydroxyl value 24 mg KOH / g, terminal ethylene oxide addition, solid content 100% by mass) <Polyisocyanate component (A2)> Biuret hexamethylene diisocyanate (NCO content 23.5%, solid content 100% by mass)

[0072] <Powder component (B)> Powder 1: Titanium oxide Powder 2: Ground calcium carbonate Powder 3: Melamine-coated ammonium polyphosphate Powder 4: Fatty acid (stearic acid and palmitic acid) coated ammonium polyphosphate (fatty acid coating rate: 3% by mass) Powder 5: Fatty acids (stearic acid and palmitic acid) and melamine-coated ammonium polyphosphate (fatty acid coating rate: 3% by mass) Powder 6: Melamine Powder 7: Pentaerythritol

[0073] <Curing catalyst (P)> Dibutyltin dilaurate (active ingredient (purity): 97% by weight) <Other> Additives 1: Dispersants, defoamers, etc. Additives 2: Plasticizers, diluting solvents, etc.

[0074] (Examples 1 to 7, Comparative Examples 1 to 3) The main component was prepared by mixing the (A1), (B), (P) and additives 1 and 2 in a conventional manner according to the formulation shown in Table 1. Next, the (A2) component was mixed under the following conditions to prepare a coating material, which was then subjected to the following evaluations. (Preparation of coating material) [I] Normal temperature (25℃, 60%Rh) [II] High temperature and high humidity (35℃, 90%Rh)

[0075] <Pot life evaluation> The prepared coating material was left to stand in the same environment and the viscosity was measured using a B-type viscometer (single cylindrical rotational viscometer). The evaluation criteria were the time it took for the viscosity to reach 40 Pa s, which is an indicator of the deterioration of spray paintability, and a four-level evaluation (A>B>C>D: poor). A: More than 6 hours B: 4 hours or more C: More than 2 hours D: Less than 2 hours

[0076] <Thickening evaluation> The test specimen was an L-shaped (equal-legged) steel plate (thickness 1.6 mm x outer dimensions A 150 mm x outer dimensions B 150 mm) that had been previously coated with a rust-preventive coating. The coating material was spray-coated (one coat) to a dry film thickness of 3 mm under the following coating environment, and then cured (24 hours, 7 days). Coating environment (coating and curing conditions): [I] Normal temperature (25℃, 60%Rh) [II] High temperature and high humidity (35℃, 90%Rh) The condition of the formed coating was visually inspected and evaluated on a four-level scale (A>B>C>D: poor), with a uniform coating being rated as "A" and cracks appearing in the coating at corners and other locations being rated as "D."

[0077] [Table 1]

Claims

1. A coating material comprising a polyol component (A1) and a polyisocyanate component (A2) as a coating-forming component (A), and further comprising a powder component (B), The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The coating material, characterized in that the powder component (B) contains a powder (B-1) coated with a fatty acid.

2. 2. The coating material according to claim 1, wherein the powder (B-1) is contained in an amount of 2 to 80 mass% based on the total amount of the powder component (B).

3. A base material containing the polyol component (A1) and the powder component (B); A curing agent containing the polyisocyanate component (A2); 3. The coating material according to claim 1, which is a multi-component coating material having the following formula:

Citation Information

Patent Citations

  • Two-pack coating composition

    JP2000109753A